Analysis of Laminar Boundary Layer Equations - R. I. Yesman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes methodology for analysis and calculation of laminar fluid flow processes in a boundary layer.The presented dependences can be used for practical calculations while power carriers of various application are moving in the channels of heat and power devices.